Introduction to the legal system of the European Union - Raworth, Philip (Oceana Pub. Dobbs FerryUS, 2001)
Looks at the evolution of the European Union, its structure, its bodies and institutions. Focuses on the European Union's legal order and the decision-making process. Examines the exercise of state power and the nature of the European Union.